A randomized controlled trial on effects of different hemostatic sponges in posterior spinal fusion surgeries. Issue 1 (December 2016) - Xu, Derong; Ren, Zhinan; Chen, Xin; Zhuang, Qianyu; Sheng, Lin; Li, Shugang
Abstract Background Spinal fusion surgery is associated with significant blood loss, which may result in potential clinical complications, it is necessary to take safe and effective measures to reduce blood loss in surgery. We perform this study to assess the impact of three different hemostatic materials on perioperative blood loss. Methods We performed a Randomized Controlled Trial research and recruited patients with lumbar disease into the study between November 2013 and March 2015. All the participants were randomly assigned to 3 groups using a simple equal probability randomization scheme: Group A (Stypro hemostatic sponge), Group B (Collagen hemostatic sponge) and Group C (gelatin sponge). We compared postoperative blood loss between these 3 groups. Results In our study, drainage volume in the first 24 h of patients in Group A and B is significantly smaller, as well as total postoperative volumes of drainage (p  < 0.05) during their hospital stay. The drainage volumes in the second 24 h were similar in the 3 groups. We also found that the average drainage Hematocrit (HCT) reduced over time, the average HCT of drainage is 18.04% and 11.72% on the first day and on the second day respectively. Conclusions Hemostatic collagen sponge demonstrated better hemostasis effects than gelatin sponge with lower volume of postoperative drainage volume and blood loss in posterior spinal fusion surgery. Trial registration The trial registration number (TRN) of the study isISRCTN29254316 and date of registration is 25/10/2016. Our trial was registered retrospectively.